2022
DOI: 10.3390/nano12030298
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Purification, and Characterization of Carbon Dots from Non-Activated and Activated Pyrolytic Carbon Black

Abstract: In this work, carbon dots were created from activated and non-activated pyrolytic carbon black obtained from waste tires, which were then chemically oxidized with HNO3. The effects caused to the carbon dot properties were analyzed in detail through characterization techniques such as ion chromatography; UV–visible, Fourier-transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), and Raman spectroscopy; ζ potential; transmission electron microscopy (TEM); and spectrofluorometry. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 95 publications
1
36
0
Order By: Relevance
“…Recently, CNDs have been synthesized using a combination of bottom-up and top-down approaches, pyrolyzing in the first instance the organic precursors, converting them into carbon-based materials, followed by chemical oxidation treatment, to break down the bulk carbon into small particles with oxygenated functional groups. , This combined approach presents several advantages compared to other methods: it can be applied to a broad range of carbon-rich precursors, it allows large-scale production, and it permits achievement of high purity and product yield . Furthermore, it reduces the processing time and required post-treatments compared with other methods such as hydrothermal …”
Section: Introductionmentioning
confidence: 99%
“…Recently, CNDs have been synthesized using a combination of bottom-up and top-down approaches, pyrolyzing in the first instance the organic precursors, converting them into carbon-based materials, followed by chemical oxidation treatment, to break down the bulk carbon into small particles with oxygenated functional groups. , This combined approach presents several advantages compared to other methods: it can be applied to a broad range of carbon-rich precursors, it allows large-scale production, and it permits achievement of high purity and product yield . Furthermore, it reduces the processing time and required post-treatments compared with other methods such as hydrothermal …”
Section: Introductionmentioning
confidence: 99%
“…The behavior of the samples can be explained by the molecular interactions between the polymer chains and the gCDs present in the dispersion: in the neat CAS–HMP matrix, the random orientation of casein and pectin chains is rapidly aligned in the direction of the flow as the shear rate increases, resulting in poor interactions among the chains and lower viscosity values at higher shear rates. However, the addition of gCDs to the medium can promote the formation of agglomerates due to the morphology of the nanoparticles [ 19 ] and/or to the solvent in which the compounds are suspended [ 20 ], leading to an increase in the viscosity of the sample. Similar results were observed by Mohd et al in polyacrylamide suspensions enriched with nanoparticles [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al [ 60 ] reported that there was no standard for the dialysis time or the selection of the molecular weight cutoff (MWCO) of the dialysis membrane. González-González et al [ 61 ] performed the purification of CDs via the ultrafiltration and dialysis processes by using the Spectra-Por ® Float-A-Lyzer ® G2 with a membrane of 3.5–5 kDa. A Dionex ICS-1600 Ion Chromatography System was used after the dialysis process to ensure the complete purification of CDs.…”
Section: Preparation and Modification Of Cdsmentioning
confidence: 99%